Advances in Traffic Transportation and Civil Architecture PROCEEDING OF THE 5TH INTERNATIONAL SYMPOSIUM ON TRAFFIC TRANSPORTATION AND CIVIL ARCHITECTURE (ISTTCA 2022), SUZHOU, CHINA, 19-20 NOVEMBER 2022 - Liu, Run; Qi, Chongchong; Law, Teik-Hua (CRC Press, 2023)
Advances in Traffic Transportation and Civil Architecture focuses on the research of traffic infrastructure. This proceedings gathers the most cutting-edge research and achievements, aiming to provide scholars and engineers with apreferable research direction and engineering solutions as reference. Subjects in this proceedings include: - Road Engineering- Bridge Engineering- Tunneling- Construction Technology and Processes The works of this proceedingsaim topromote the development of civil engineering and construction technology. Thereby, promote scientific information interchange between scholars from the top universities, research centers and high-tech enterprises working all around the world.